Effectiveness and Overall Safety of NutropinAq® for Growth Hormone Deficiency and Other Paediatric Growth Hormone Disorders: Completion of the International Cooperative Growth Study, NutropinAq® European Registry (iNCGS) - Coutant, Regis; Bosch Muñoz, Jordi; Dumitrescu, Cristina Patricia; Schnabel, Dirk; Sert, Caroline; Perrot, Valerie; Dattani, Mehul (Frontiers in Endocrinology, 2021)
Objective The International Cooperative Growth Study, NutropinAq® European Registry (iNCGS) (NCT00455728) monitored long-term safety and effectiveness of recombinant human growth hormone (rhGH; NutropinAq® [somatropin]) in paediatric growth disorders. Methods Open-label, non-interventional, post-marketing surveillance study recruiting children with growth disorders. Endpoints included gain in height standard deviation score (SDS), adult height, and occurrence of adverse events (AEs). Results 2792 patients were enrolled. 2082 patients (74.6%) had growth hormone deficiency (GHD), which was isolated idiopathic in 1825 patients (87.7%). Non-GHD diagnoses included Turner syndrome (TS) (n=199), chronic renal insufficiency (CRI) (n=10), other non-GHD (n=498), and missing data for three participants. Improvements from baseline height SDS occurred at all time points to Month 132, and in all subgroups by disease aetiology. At Month 12, mean (95% CI) change in height SDS by aetiology was: idiopathic GHD 0.63 (0.61;0.66), organic GHD 0.71 (0.62;0.80), TS 0.59 (0.53; 0.65), CRI 0.54 ( 0.49;1.56), and other non-GHD 0.64 (0.59;0.69). Mean height (±SD) at the last visit among the 235 patients with adult or near-adult height recorded was 154.0 cm (±8.0) for girls and 166.7 cm (±8.0) for boys. The most frequent biological and clinical non-serious drug related AEs were increased insulin like growth factor concentrations (314 events) and injection site haematoma (99 events). Serious AEs related to rhGH according to investigators were reported (n=30); the most frequent were scoliosis (4 events), epiphysiolysis (3 events), and strabismus (2 events). Conclusions There was an improvement in mean height SDS in all aetiology subgroups after rhGH treatment. No new safety concerns were identified.